1999
DOI: 10.1097/00000658-199906000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemic of Cocaine-Related Juxtapyloric Perforations

Abstract: Juxtapyloric perforations after the smoking of crack cocaine occur in a largely male population of drug addicts who are 8 to 10 years younger than the patient group that historically has perforations in the pyloroduodenal area. These perforations are usually 3 to 5 mm in diameter, and an antral mucosal biopsy for subsequent urease testing should be performed if the location and size of the ulcer allow this to be done safely. Omental patch closure is appropriate therapy for patients without a history of prior u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Feliciano et al have reported cocaine induced gastro-intestinal perforations and these events are said to be due to co-existing H.pylori infection leading to mucosal weakness, which is then exacerbated by valsalva action (5). Our case report demonstrates evidence of inflammation of the oesophagus, and low probability of a lung injury in the setting of pneumomediastinum secondary to cocaine use.…”
Section: Discussionmentioning
confidence: 99%
“…Feliciano et al have reported cocaine induced gastro-intestinal perforations and these events are said to be due to co-existing H.pylori infection leading to mucosal weakness, which is then exacerbated by valsalva action (5). Our case report demonstrates evidence of inflammation of the oesophagus, and low probability of a lung injury in the setting of pneumomediastinum secondary to cocaine use.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies reported use of falciform ligament in gastrointestinal surgery with most common technique employing falciform ligament in perforated gastric or intestinal ulcer as an alternative to graham patch. 1,[6][7][8][9][10][11] A total of 14 patients underwent falciform ligament for intestinal perforation. No mortalities were reported, and no studies reported technical complications or unplanned returns to the operating room.…”
Section: Gastrointestinal Surgerymentioning
confidence: 99%
“…Intake of nonsteroidal anti-inflammatory drugs is found in about half of cases of perforated ulcers. Cocaine was shown as an important causative factor in perforated juxtapyloric ulcers in a series of patients from an urban hospital (Feliciano et al 1999). Other rarer causes are associated with an increased prevalence of digestive ulcer, such as Zollinger-Ellison syndrome, in which ulcers are more likely jejunum ulcers, and Crohn disease.…”
Section: Gastroduodenal Perforationmentioning
confidence: 99%